Towards a shared vision of language, language learning, and a school project in emergence. Issue 4 (2nd October 2021) - Tumelius, Riikka; Kuure, Leena
ABSTRACT: Technology development allows new ways of communication, learning and collaboration. This is reflected in the professional scenarios of language teaching. Modern curricula value participants' interest and meaningful (inter)action as a basis for learning. Sensitivity is important in anticipating participants' changing needs in modern learning environments, characterised by linguistic and technological hybridity, as well as novel pedagogical approaches. Language students, more familiar with teaching in the traditional classroom, need to appropriate new practices to orchestrate learning in settings requiring multiple activities simultaneously. This study explores how language students learn to manage complex pedagogical situations during a university course in which they create an online project for school children. During online chat sessions administered for the school pupils, the university lecturer's office was an important site for negotiating and acting on pedagogical issues as well as practical matters arising from the work at hand. Nexus analysis was used as a research approach. Primary research materials include video recordings from the university lecturer's office, chatlogs and reflection papers from students. The study is relevant for reconceptualising the changing roles of (language) teachers and provides new perspectives for language teacher education in a technology-rich world.